Multifunctional PLGA/collagen/zeolitic imidazolate framework-8 composite nanofibrous membranes for guided bone regeneration - Tianqi Wang; Qi Xie; Hongbo Liang; Yu Sun; Weili Xie (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionGuided bone regeneration (GBR) is widely used for maxillofacial defects, but fabricating membranes that enhance osteoinduction and antimicrobial resistance remains challenging. This study addresses critical bone defect therapy by developing collagen (Col) and zeolitic imidazolate framework-8 (ZIF-8) reinforced poly(lactide-co-glycolide) (PLGA) nanofibrous membranes.MethodsMaterial characterization analyzed the composite nanofibrous membranes’ morphology, structure, wettability, tensile strength, in vitro degradation, and ion release. Biocompatibility and osteogenesis were evaluated using live/dead staining, cytoskeleton staining, CCK-8 assay, alkaline phosphatase (ALP) activity quantification, ALP staining, alizarin red S (ARS) staining and ARS quantification. Antibacterial efficacy was assessed via agar plate counting and bacterial growth kinetics. In vivo bone regeneration was examined in a rat cranial critical defect model treated with the membrane; bone formation was evaluated by Micro-CT and hematoxylin-eosin staining after 4 weeks.ResultsOptimization of the PLGA/Col weight ratio (100:3) yielded composite membranes demonstrating superior tensile strength. The PLGA/Col/ZIF-8 nanofibrous composite incorporating 1 wt% ZIF-8 nanoparticles exhibited optimal biocompatibility with sustained Zn2+ release kinetics. In vitro experiments demonstrated that sustained release of Zn2+ has the dual effects of stimulating osteogenic differentiation and effectively preventing early bacterial infection. In vivo a rat calvarial defect model further confirmed the positive bone regeneration effect of the PLGA/Col/ZIF-8 composite nanofibrous membrane.DiscussionPLGA/Col/ZIF-8 composite nanofibrous membranes have great potential for application in guiding bone tissue regeneration.